Science Education in the Family Environment with the Experimental Method of Facial Cosmetics Plant Fertilization in the Covid-19 Pandemic Era - Nursetiawati, S.; Josua, D. P.; Atmanto, D.; Oktaviani, F.; Fardani, A. L. (Jurnal Pendidikan IPA Indonesia, 2020)
The physical and non-physical family environment is one of the most critical factors in student learning outcomes. This research was assessed using a mixed-method descriptive qualitative and quantitative method to see how the family environment, both physical and non-physical, with experimental science learning was conducted on 60 Junior High School students. The requirements of the respondents in this study were 30 open school students and 30 non-open school students. The results showed that: (a) family involvement motivates students when conducting experiments; (b) the feasibility of the physical environment of the family allows students to complete the experiment of making simple liquid fertilizers to the application of these fertilizers to cosmetic plants, (c) students can complete the experiment by giving directions to the online method because of the high involvement family in the learning process. Other studies state that the family environment in the form of parents ‘expectations of students’ future careers in science is the main reason for high family participation in the experimental process to provide maximum student experimental results. In conclusion, the family’s physical and non-physical environment dramatically determines and encourages students to optimize experimental science learning methods so that science education applied during the Covid-19 pandemic by studying at home can be continued and carried out experimentally. The New Normal Education Model through online and non-online methods for science learning can still be done at home, with the involvement of the family’s physical and non-physical environments that support students to complete experiment-based science learning projects. Independent learning in junior high school students can also be done by providing direct control between educators and the students’ non-physical environment, namely parents, to remain motivated.